Kultum Tarawih Ramadhan Momentum Dalam Menyebarkan Dakwah - Oki, Alber; Yarjuna; Hidayatullah; Ramadhan, Rafly; Iskandar, Nur Muhammad Ikandar (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2023)
The tarawih cultum is a short lecture delivered before or after the tarawih prayer, which is a momentum in conveying religious messages to the tarawih prayer congregation. The purpose of this service is to describe the role of tarawih cultum as a means of spreading da'wah. This service uses a descriptive analysis method to describe the role of the Tarawih Kultum. The results of the service show the role of the tarawih cultum for Muslims in increasing devotion in the holy month of Ramadan and adding insight into Islam which is an obligation for every Muslim.